2008
DOI: 10.1016/j.joen.2008.02.005
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Generation of Dental Pulp-like Tissue by Using Dental Pulp Stem Cells, a Collagen Scaffold, and Dentin Matrix Protein 1 after Subcutaneous Transplantation in Mice

Abstract: The presence of a perforation is known to significantly compromise the outcome of endodontic treatment. One potential use of regenerative endodontic therapy may be the repair of root canal perforations. In addition to nutrients and systemic in-situ interactions, the three main components believed to be essential for tissue regeneration are: stem cells, scaffold, and growth factors. This study investigated the role of each component of the tissue engineering triad in the organization and differentiation of Dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
199
0
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(218 citation statements)
references
References 34 publications
(39 reference statements)
4
199
0
15
Order By: Relevance
“…22 In a subcutaneous transplantation mice model, DMP1 has been shown to induce the generation of dental pulp-like tissue when combined with dental pulp stem cells and a collagen scaffold. 23 However, to date, little is known about the effects of these NCPs on bone tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…22 In a subcutaneous transplantation mice model, DMP1 has been shown to induce the generation of dental pulp-like tissue when combined with dental pulp stem cells and a collagen scaffold. 23 However, to date, little is known about the effects of these NCPs on bone tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Both cell-based and cell-homing approaches showed various aspects necessary for pulp regeneration (14)(15)(16). Some of these studies already focused on the use of irrigating solutions (10,17) and the type of scaffold (18)(19)(20). In the current study, the fibrin gel showed distinctive tissue in-growth without cell transplantation.…”
Section: Discussionmentioning
confidence: 63%
“…[10][11][12] This versatile material also finds its application in the field of plastic surgery, oral and maxillofacial surgery and dentistry for various purposes e.g. as an interpositional graft material during palatoplasty; [13] for guided bone regeneration during maxillary sinus lift; [14] for inducing bone formation along with/without certain medicaments like gusuibu; [15,16] bone augmentation of posterior atrophic mandibular ridge for placement of dental implants; [17] as a reconstructive material for orbital floor fractures; [18] in treatment of localized gingival recession; [19] as a scaffold in tissue engineering to generate dental pulp; [20] for coverage of small intraoral soft tissue defects of the oral cavity [21] and much more. Collagen also has use as a medium for culturing cells such as osteoblasts.…”
Section: Collagen As a Biomaterials In Plastic And Reconstructive Surgerymentioning
confidence: 99%